Education and training on dental and oral health as well as clean and healthy lifestyle for children - Naufal Hanif Syah Novildan; Dita Syifa Khairunnisa; Mierzha Argiyan Giovan; Dwi Aji Nugroho; Sri Utami; Sartika Puspita (Community Empowerment, 2024)
Oral health status remains a pressing concern in Indonesia, demanding urgent attention. This stems from low public awareness and understanding of the significance of dental care, high treatment costs, and a tendency among dental practitioners to prioritize treatment over prevention. This community service initiative aimed to enhance knowledge, awareness, and promote healthy lifestyle habits among children in Dusun Pakelan, Desa Sumberarum, Moyudan, Sleman, DIY. The implementation method involved five stages: education and practice of Healthy Lifestyle and Behavior (PHBS), counseling and practice of oral health (KESGILUT), distribution of free toothbrushes and toothpaste, and group exercise. The outcomes revealed a 15.17% improvement in children's knowledge, awareness, and skills regarding oral cavity hygiene. Healthy lifestyle behaviors also witnessed an improvement, with an 8.95% increase in knowledge.